2021
DOI: 10.3389/fphar.2021.631897
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effect of Different Concentrations of Epidural Ropivacaine Alone or Combined With Sufentanil in Patients After Cesarean Section

Abstract: Background: Patients experience moderate-high intensity postoperative pain after cesarean section (CS). The aim of this study was to investigate the optimal concentrations of ropivacaine and sufentanil for use in controlling pain after CS.Methods: One hundred and seventy-four women undergoing elective CS were randomly allocated to four groups. Epidural analgesia was administered with 0.1% ropivacaine in the R1 group, 0.15% ropivacaine in the R2 group, a combination of 0.1% ropivacaine and 0.5 μg/ml of sufentan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Epidural co-administration of 0.15% ropivacaine and 0.5 µg/mL sufentanil for pain control after cesarean section exhibited lower numerical rating scale (NRS) scores and higher patient-satisfaction scores. 21 In this study, the sufentanil and ropivacaine combination resulted in a higher degree of parturient self-motor control and pain relief, but not absolute satisfaction. Notably, the Apgar scores at 5 and 10 mins were 10 for almost all neonates.…”
Section: Discussionmentioning
confidence: 59%
“…Epidural co-administration of 0.15% ropivacaine and 0.5 µg/mL sufentanil for pain control after cesarean section exhibited lower numerical rating scale (NRS) scores and higher patient-satisfaction scores. 21 In this study, the sufentanil and ropivacaine combination resulted in a higher degree of parturient self-motor control and pain relief, but not absolute satisfaction. Notably, the Apgar scores at 5 and 10 mins were 10 for almost all neonates.…”
Section: Discussionmentioning
confidence: 59%
“…Care should be taken to monitor fluid administration to prevent fluid overload (17) . In this case, we administered post-caesarean analgesia in the form of Levobupivacaine to reduce post-cesarean pain, which can cause impaired milk production in patients and reduced quality of neonatal care (18) .…”
Section: Fentanyl Is Used As An Adjuvant Tomentioning
confidence: 99%
“…Unfortunately, epidural opioid (e.g., morphine) analgesia could be associated with complications, including postoperative nausea and vomiting (PONV), pruritus, respiratory depression, etc., which hinder early recovery after CS ( Guasch et al, 2020 ). Multiple studies have demonstrated that analgesia is more effective and some annoying side effects are minimized when opioids are administered in combination with local anesthetics ( Yang et al, 2019 ; Miao et al, 2021 ; Otao et al, 2021 ). Notably, this multimodal approach has been shown to provide superior analgesia to that of intramuscular or intravenous administration of opioids without significant side effects ( Stocki et al, 2014 ; Yang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%